External debt and economic growth nexus in a small island developing state: An Autoregressive Distributed Lag Model investigation - Fauzel, Sheereen; Jugreet, Fariiha (The journal of contemporary issues in business and government, 2019)
This study investigates the nature of the relationship between external debt and growth in Mauritius and seeks to explore whether macroeconomic policies affect this nexus. The Autoregressive Distributed Lag Model bound testing approac h is employed on the time series data for the period of 1980 to 2016. The findings showed a negative relationship between external debt and growth, confirming the presence of debt overhang. A crowding out effect was also found since debt servicing had a negative effect on growth. On the other hand, when an interactive term of debt and good policy is introduced, the negative effect of external debt on growth is lower, reducing the debt overhang problem and leading to a weak crowding out effect. However, the use of such economic policy has negative consequences on domestic investment and trade.